Тhe influence of the removal bee pollen with the pollen catcher on the flight activity and behaviour of the bees-polen collectors - Mishchenko O.; Lytvynenko O.; Afara K.; Kryvoruchko D. (Технологія виробництва і переробки продуктів тваринництва, 2021)
The possibility of demonstration of the productivity potential of the bee families depends directly on the level of provision of protein feed. In this regard, the study of the bees behavior that is connected to harvesting and processing of protein food is important for both biology and practical beekeeping. The presented work provides some data of experimental studies of the influence of the removal of the bee pollen on the flight activity of bees. The study of the ethological features that enhance the increase of collection, harvesting and processing of the protein feed was conducted. With this purpose the studies were conducted to elucidate the factors that induce collection of the protein feed -bee pollen by bees and its harvesting in the nest of the bee family in the form of the bee bread. The factors that influence the increase of the collection of the protein feed by bees were researched on experimental and control bee families- analogues. Throughout the studies it was identified that the bees with medium strength were the most active in collecting the pollen. The removal of the bee pollen with pollen catchers decreases the raising of brood by bee families, but doesn’t result in their significant weakening. With the enlargement of the area of the open brood the collection of the pollen by bees increases. In order to obtain the saleable bee pollen the strong bee families should be kept on the apiary. The bees-collectors of the protein feed have the individual features of collecting the bee pollen. With the removal of thbrood from the nest the activity the bees that flew out decreased. When adding the open brood the activity increased. On the contrary, with supply of the bee pollen to the nest, the pollen collecting activity decreases and adding the carbohydrates has no effect. The removal of the bee pollen with the pollen catcher from the bee families increases the flight activity which in turn leads to obtaining more bee pollen on the apiaries and pollination of additional quantity of entomophilous plants. In order to obtain the saleable bee pollen the strong families should be kept on the apiary and the removal should be conducted in the morning and day hours.